Kültürlerarası iletişim sorunları ve çözümleme becerisiyle turizmde alternatif pazar oluşumu - SEMİZ ÇELİK, DERYA (My University, 2021)
Ülke ekonomilerinde önemli bir gelir kaynağı olan turizm sektörü çevresel faktörlere oldukça duyarlı pazarlardır. Bu duyarlılık önemsenmemesi halinde ciddi pazar kayıplarına sebebiyet vermektedir. Pazar oluşumun zorluğu göz önüne alındığında mevcut pazarın kaybına izin verilmemesi gerekilmektedir. Turizmde yaşanılan öncül sorun farklı kültürlerin karşılaşmasıdır. Çeşitli amaçlar ile seyahat eden bir turist içine girdiği faklı kültürden bir toplum içinde zorluklar yaşayabilmekte hatta yaşadığı ya da yaşayabileceği sorun sebebiyle seyahatinden vazgeçebilmektedir. Kültürlerarası iletişimin sebep olacağı sorunlar ve ülkelerin bu sorunları çözümleme becerileri turistlerin olumsuz olan ya da olabilecek algılarını yenerek turizm pazarlarını devam ettirebilecek hatta yeni pazarlar oluşturmalarını sağlayacaktır. Bu amaçla bu çalışmada kültürlerarası farklılıklardan kaynaklı yaşanabilecek sorunlar, bu sorunlar karşısındaki tutumlar değerlendirilmiştir. Bu doğrultu da sorunlar karşısında geliştirilecek çözüm yolları ile turistlerin tutum ve davranışlar kültürel iletişim sorunlarını çözme anlamında kontrol altına alınabilecektir. Kontrol edilebilen pazar davranışları ile gerek mevcut pazarı koruma gerekse yeni pazar oluşturmaya ciddi destek sağlayacaktır.

The growing ability to act jointly in all of the growing and developing world markets is an important element for all businesses. In the priority process of being able to fulfill this element is to strengthen communication. Transmission comes at the forefront of questions and problems that may arise in the encounter of different cultures. Solving the problems that may arise from differences in communication between cultures is also possible with the development of problem solving skills of the enterprises. Solving these problems will allow businesses to both protect their existing markets and allow for new market developments. Purpose;In order to be able to solve the problems arising from the cultural differences, firstly what problems can be encountered should be evaluated. This evaluation varies by institution and sector. In this study, tourism, which is the sector in which intercultural communication encounters are most experienced, is dealt with. After a short survey of literature in the study, the questionnaire study and evaluation were included. Purpose of Implementation; It was questioned what the communication problems arising from the intercultural differences of the tourists traveled and what their stance towards these problems might be. Depending on the attitudes and behaviors of the potential problems of the tourists, it was aimed both to maintain tourism in the market and to develop solutions for what could be done to create an alternative market. methodology;In the questionnaire, 312 questionnaires were obtained from tourists who came to Istanbul for the first time or Turkish citizens who traveled at least once outside the country. The problems encountered in the obtained data were mainly evaluated under two headings as reactions to the problems. The method used in practice; The data obtained with the questionnaire prepared according to the aims stated above were analyzed with the help of the SPSS 16 program. In addition to the general statistical evaluations, the responses of tourists to the problems arising from cultural differences were evaluated with comparative tables. Findings (Results);The survey results show that tourists are not unresponsive to the problems they face. It has been seen that they have not only abandoned the market but also told the people in their surroundings that they should not come. The awareness that the problem arises from cultural differences seems to alleviate the reaction, but it does not change tourists' perceptions of negative thinking. This can lead to serious market losses. The fact that the problems can be resolved will allow the satisfaction of tourists to improve the market and allow for new market developments that can be marketed in the country. the conclusionanddiscussio; The development of the market in tourism and the difficulty of enlargement cause a serious problem which is caused by cultural differences and causes a bad intention. The purpose of the tourism market is also changing the point of view of the problems. It is seen that tourists who travel for business are less concerned with the problems that cultural differences will have compared to other tourists. Increasing the level of education also seems to increase the sensitivity to the problems.
Alternative market formation in tourism with problems of intercultural communication and analysis skills
Keywords: Tourism; Tourism Markets; Tourism Market Problems; Communication Skills; Intercultural Communication; Turizm; Turizm Pazarları; Turizm Pazar Sorunları; İletişim Becerisi; Kültürlerarası İletişim